Where does research design fall short? Mental health related‐stigma as example. (3rd February 2022) - Walsh, Daniel; Foster, Juliet
Abstract: Efforts to challenge mental health‐related stigma have been limited by an insufficient conceptualization of the problem space. As is common in health communication, practitioners have neglected the multiple tacit understandings the public embody in everyday life. Using the example of our recent research into the public's social representations of mental health and illness, in this paper, we will work through the theoretical‐methodological considerations involved in how we approached expanding the problem space. Using social theory, we tailored thematic analysis and natural language processing techniques to examine the public's polyphasic sense‐making processes. The approach is novel, as it diverges from standard methods in understanding health communication and the possibilities for behaviour change. Instead, we root our approach in a dynamic and relational epistemology to iteratively reveal in greater complexity some of the contents and processes that sustain mental health‐related stigma.